2013
DOI: 10.2320/matertrans.m2013285
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Removal from Mine Tailings for Recycling via Flotation

Abstract: In this study, we propose a flotation process to remove the arsenic from Samkwang mine tailings in South Korea, which contained a high arsenic content, in order to render them suitable for recycling. In order to maximize the arsenic removal from the mine tailings, three variables (type of collectors and activators, and solution pH) were systematically investigated. Characterization experiments (X-ray diffraction and electrokinetic property analyses) were carried out to complement the flotation results, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…During this process, a collector is used to impart hydrophobicity to desired mineral particles; these hydrophobic particles are then better attached onto the surface of a bubble, leaving undesired particles in the bulk solution. Among these collectors is xanthate, which is a typical collector used for sulfide minerals and for oxide minerals after the sulfidization process [7][8][9][10]. Although this collector has been exploited extensively over the last several decades, a reduction in its use is desired because it is environmentally harmful [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…During this process, a collector is used to impart hydrophobicity to desired mineral particles; these hydrophobic particles are then better attached onto the surface of a bubble, leaving undesired particles in the bulk solution. Among these collectors is xanthate, which is a typical collector used for sulfide minerals and for oxide minerals after the sulfidization process [7][8][9][10]. Although this collector has been exploited extensively over the last several decades, a reduction in its use is desired because it is environmentally harmful [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…1,2) In particular, the sul de minerals (e.g., chalcopyrite, galena, and sphalerite) associated with the subject metal possess similar surface properties (e.g., electrokinetic and hydrophobic properties). [3][4][5][6][7][8][9] Fullston and the colleagues reported that the electrokinetic property of intact sulde minerals such as pyrite, sphalerite, chalcopyrite, and galena is similar with that of elemental sulfur, and thus they have similar isoelectric points lower than 3. 3,4) Depending on the magnitude of polarity (i.e., the strength of bonding composed of minerals), minerals can be subdivided into ve categories; 5) sul de minerals have a weak covalent bonding that is relatively weaker than that of carbonate, sulfate, and oxide minerals, and the low surface polarity caused by the weak bonding structure renders the surface of sul des relatively hydrophobic.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, due to the aforementioned reasons that sul de minerals possess similar surface properties, separating each other is not straightforward. In most studies, hence, the recovery and grade have been improved by introducing effective or novel depressants.…”
Section: Introductionmentioning
confidence: 99%
“…20,21) Previous studies reported that dixanthogen has a range of E H that exists very stably. 9,26) Accordingly, to examine the correlation between floatability and E H in the present study, the floatability of arsenopyrite and pyrite was plotted with the E H function in Fig.…”
Section: Analysis Of Correlation Between the Change Of Pulp Potentialmentioning
confidence: 99%
“…Here, it should be noted that although the peak of quartz was observed for both minerals, the effect of minimal amount of silica on the present study is negligible due to the unfavorable interaction between quartz and xanthate as supported by many previous studies. 20,21) To perform the flotation experiment, arsenopyrite and pyrite were crushed under 8 mesh (2.36 mm, Tyler Standard) using a jaw and cone crusher, and a single disc mill was used to grind it to have a particle size distribution of ¹105 + 150 mesh (106150 µm, Tyler Standard). To prevent mineral surface oxidation, the sample was preserved at freezing status.…”
Section: Materials and Reagentsmentioning
confidence: 99%